The Accessibility of Dental Health Services for Consumers/Patients Aged 60+ Against the Extent to Which Health Needs Are Met in the Post-COVID Period - Klaczek-Suchecki, Kajetan (Journal of Public Governance, 2024)
Objective: Human health needs increase with age. Hence, people aged 60+ are among the main beneficiaries within the health care system. At the same time, payment for dental services can be a significant barrier for older people, who usually do not have a considerable disposable income, which may limit their consumption in this area. The aim of this study is to determine consumers’/patients’ aged 60+ accessibility of dental services in relation to their reported level of satisfaction of health care needs. Research Design & Methods: The paper is based on an analysis of the legal acts concerning the basket of guaranteed benefits for dental prevention and treatment, as well as on an analysis of the results of a primary research study using an online survey carried out on a research sample of 1,100 people in the Ariadna National Research Panel in November 2022. Findings: Income barriers and public payer regulations result in limitations on seniors’ accessibility to dental services, which can result in negative population health outcomes. Recommendations: The consequence of the described state of affairs can include further costs for the public payer related to the emergence of conditions resulting from previously unmet health needs. Thus, the cost-effectiveness of services should be assessed not only from the point of view of current needs, but also with regard to preventive measures concerning the emergence of more costly conditions. Article classification: research article JEL classification: D12, I13, H2